Psychopharmacology of agitation in acute psychotic and manic episodes. Issue 3 (11th May 2022) - Stetson, Sean R.; Osser, David N.
Abstract : Purpose of review: To provide updated guidance for the medication treatment of acute agitation in the setting of psychosis or mania on inpatient psychiatric units. Recent findings: This topic presented challenges: studies are sparse, tend to be under-powered, and are difficult to compare. Though there have been few recent studies, there have been several recent meta-analyses, Cochrane reviews, and published guidelines that sift through the primarily older evidence as well as more recent trials. The reviewers often do not agree on what seems to have the best evidence for efficacy and safety. Summary: We conclude that the best approach is to summarize in some detail the evidence for each possible treatment and the interpretations published recently on each of those treatments, and then present recommendations for medication management in tiered rankings, based on the authors' qualitative review of the data and opinions. For oral treatment, the first-tier options are (alphabetically) haloperidol with lorazepam, lorazepam alone, and olanzapine. The second tier includes haloperidol with promethazine, loxapine inhaler, and risperidone alone. Tier 3 includes asenapine and quetiapine. For intramuscular treatment, the first-tier includes haloperidol plus promethazine, and olanzapine alone, and the second-tier includes haloperidol with lorazepam, and lorazepam alone.